2019
DOI: 10.18502/ijph.v48i5.1829
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Strengths and Challenges related to Health on the First 10 Days after the Large Earthquake in the West of Iran, 2017

Abstract: Background: The objective of the present study was to investigate the strength and weaknesses of healthcare management during the first 10 days after the earthquake in Sarpol-e Zahab in Kermanshah, Iran. Methods: This qualitative, observational study was conducted on November 13-23, 2017 in the disaster area, by using content analysis. Data was collected through experts and focus group interviews with professional and healthcare staff, and policy-makers. Results: Our findings were categorized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…According to some studies, mental health risk factors such as depression for disasters are different in children and adults; hence, being under rubble, experiencing fear and injury, witnessing the others' injury and death, and noticing weaknesses in the social support system would lead to more severe cases of depression in children (Tang, Liu, Liu, Xue, & Zhang, 2014). Recent studies on Iranian earthquake victims have also indicated that, especially in ten days after the earthquake, the main health needs of earthquake victims were a healthy environment, mental health, and mother and infant and child health, as well as health care requirements such as eld hospital, medicine, and epidemic diseases (Peyravi, Ahmadi Marzaleh, & Khorram-Manesh, 2019). Furthermore, more recent studies on resilience also indicate that environmental and social factors, in addition to personal traits, play a key role in recovering the injured person and his growth, especially in younger ages (Amini-Tehrani et al, 2020;Ungar, Ghazinour, & Richter, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, mental health risk factors such as depression for disasters are different in children and adults; hence, being under rubble, experiencing fear and injury, witnessing the others' injury and death, and noticing weaknesses in the social support system would lead to more severe cases of depression in children (Tang, Liu, Liu, Xue, & Zhang, 2014). Recent studies on Iranian earthquake victims have also indicated that, especially in ten days after the earthquake, the main health needs of earthquake victims were a healthy environment, mental health, and mother and infant and child health, as well as health care requirements such as eld hospital, medicine, and epidemic diseases (Peyravi, Ahmadi Marzaleh, & Khorram-Manesh, 2019). Furthermore, more recent studies on resilience also indicate that environmental and social factors, in addition to personal traits, play a key role in recovering the injured person and his growth, especially in younger ages (Amini-Tehrani et al, 2020;Ungar, Ghazinour, & Richter, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of women, the multifactorial role of their mental health should be further examined, and the political-legal dimensions and their psychological lifestyle need to be considered comprehensively (Shooshtari, Abedi, Bahrami, & Samouei, 2018). Accordingly, the organized post-earthquake management can be considered as an effective factor in preventing further physical and psychological health complications among survivors (Peyravi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One of these faults, called Astaneh, on the northwest of Damghan, accounted for the sixth largest earthquake in the world, measuring 7.6 M and killing 200.000 (17). In previous studies which investigated the natural disasters in Iran, due to numerous faults and high seismicity in the country, earthquake is considered as the biggest hazard in the country (2,24). Additionally, in the present study, the probability of landslides following an earthquake is also higher in the mountaineer regions of three rural HCFs.…”
Section: Discussionmentioning
confidence: 99%
“…A powerful earthquake struck Kermanshah province in west of Iran near the Iran-Iraq border at 18:18:16 UTC (21,48:16 local time) on November 12, 2017. More than 600 people lost their lives, about 10,000 were injured, and thousands of building were damaged [2,12]. Consequently, thousands of the affected people were displaced in Sar-e Pul-e Zahab, Ezgeleh and surrounding villages [2], which needed urgent government and humanitarian assistance, especially in the early days of the disaster.…”
Section: Introductionmentioning
confidence: 99%